2021
DOI: 10.3390/s21186288
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Event-Based Classification Accuracy in Pit-Drilling Operations: An Application by Neural Networks and Median Filtering of the Acceleration Input Signal Data

Abstract: Forestry is a complex economic sector which is relying on resource and process monitoring data. Most of the forest operations such as planting and harvesting are supported by the use of tools and machines, and their monitoring has been traditionally done by the use of pen-and-paper time studies. Nevertheless, modern data collection and analysis methods involving different kinds of platforms and machine learning techniques have been studied lately with the aim of easing the data management process. By their out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Accordingly, the LOG LOSS was lower in the testing phase from 2 to 5.5%, while the F1 score and classification accuracy were higher in the testing phase from 0.7 to 2.3 and 0.5 to 1.6%, respectively. All of these results are coming in high contrast to those of the previous studies which have found either similar [4] or higher values of classification errors and lower values in terms of classification accuracy in the testing phase [24,52].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Accordingly, the LOG LOSS was lower in the testing phase from 2 to 5.5%, while the F1 score and classification accuracy were higher in the testing phase from 0.7 to 2.3 and 0.5 to 1.6%, respectively. All of these results are coming in high contrast to those of the previous studies which have found either similar [4] or higher values of classification errors and lower values in terms of classification accuracy in the testing phase [24,52].…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the best model architecture was selected using the first criterion, namely the error during training which was found to be the lowest for an NN architecture when using the ReLU activation function and α set at 0.01. It turns out that the best-performing models reported in other studies checking the effect of classification performance on acceleration data had similar architectures, placing the use of the ReLU activation function and of the regularization terms of up to 0.1 among the best options in terms of classification performance [24,52]. However, the performance of NN depends also on several other factors [53,54], including signal quality and other issues specific to classification tasks such as intra-class variability and inter-class similarity.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Soil disinfection combined with tillage is an effective solution to continuous cropping obstacles, which can be used to kill most of the virus bacteria in the soil at the same time as cultivation. At present, the vertical spiral blade roll has been widely used in afforestation and reforestation operations due to its reliability and ability to crush soil quickly [ 8 , 9 ]. The principle of vertical rotary tillage is precisely based on the use of the mechanical vertical spiral blade roll to grind and suspend the soil naturally, integrating the functions of plowing, harrowing, crushing, and loosening the soil.…”
Section: Introductionmentioning
confidence: 99%